Challenges for assessing vertebrate diversity in turbid Saharan water-bodies using environmental DNA - Egeter, B.; Peixoto, S.; Brito, J.; Jarman, Simon; Puppo, P.; Velo-Antón, G. (N R C Research Press, 2018)
The Sahara desert is the largest warm desert in the world and a poorly explored area. Small water-bodies occur across the desert and are crucial habitats for vertebrate biodiversity. Environmental DNA (eDNA) is a powerful tool for species detection and is being increasingly used to conduct biodiversity assessments. However, there are a number of difficulties with sampling eDNA from such turbid water-bodies and it is often not feasible to rely on electrical tools in remote desert environments. We trialled a manually powered filtering method in Mauritania, using pre-filtration to circumvent problems posed by turbid water in remote arid areas. From nine vertebrate species expected in the water-bodies, four were detected visually, two via metabarcoding, and one via both methods. Difficulties filtering turbid water led to severe constraints, limiting the sampling protocol to only one sampling point per study site, which alone may largely explain why many of the expected vertebrate species were not detected. The amplification of human DNA using general vertebrate primers is also likely to have contributed to the low number of taxa identified. Here we highlight a number of challenges that need to be overcome to successfully conduct metabarcoding eDNA studies for vertebrates in desert environments in Africa.